Antiparasitic activity of FLLL-32 against four Babesia species, B. bovis, B. bigemina, B. divergens and B. caballi, and one Theileria species, Theileria equi in vitro, and Babesia microti in mice - El-Sayed, Shimaa Abd El-Salam; El-Alfy, El-Sayed; Baghdadi, Hanadi B.; Sayed-Ahmed, Mohamed Z.; Alqahtani, Saad S.; Alam, Nawazish; Ahmad, Sarfaraz; Ali, Md. Sajid; Igarashi, Ikuo; Rizk, Mohamed Abdo (Frontiers in Pharmacology, 2023)
Introduction: FLLL-32, a synthetic analog of curcumin, is a potent inhibitor of STAT3’s constitutive activation in a variety of cancer cells, and its anticancer properties have been demonstrated both in vitro and in vivo. It is also suggested that it might have other pharmacological activities including activity against different parasites. Aim: This study therefore investigated the in vitro antiparasitic activity of FLLL-32 against four pathogenic Babesia species, B. bovis, B. bigemina, B. divergens, and B. caballi, and one Theileria species, Theileria equi. In vivo anti-Babesia microti activity of FLLL-32 was also evaluated in mice. Methods: The FLLL-32, in the growth inhibition assay with a concentration range (0.005–50 μM), was tested for it’s activity against these pathogens. The reverse transcription PCR (RT-PCR) assay was used to evaluate the possible effects of FLLL-32 treatment on the mRNA transcription of the target B. bovis genes including S-adenosylhomocysteine hydrolase and histone deacetylase. Results: The in vitro growth of B. bovis, B. bigemina, B. divergens, B. caballi, and T. equi was significantly inhibited in a dose-dependent manner (in all cases, p < 0.05). FLLL-32 exhibits the highest inhibitory effects on B. bovis growth in vitro, and it’s IC50 value against this species was 9.57 μM. The RT-PCR results showed that FLLL-32 inhibited the transcription of the B. bovis S-adenosylhomocysteine hydrolase gene. In vivo, the FLLL-32 showed significant inhibition (p < 0.05) of B. microti parasitemia in infected mice with results comparable to that of diminazene aceturate. Parasitemia level in B. microti-infected mice treated with FLLL-32 from day 12 post infection (pi) was reduced to reach zero level at day 16 pi when compared to the infected non-treated mice. Conclusion: The present study demonstrated the antibabesial properties of FLLL-32 and suggested it’s usage in the treatment of babesiosis especially when utilized in combination therapy with other antibabesial drugs.